A Short-Term Cost- Effectiveness Evaluation of Better-Quality Daycare Centers - Ricardo Barros; Mirela de Carvalho; Samuel Franco; Rosane Mendonca; Andrezza Rosalem (Inter-American Development Bank (IDB), 2011)
Studies of the effects of pre-school programs on child development in developing countries have found scant impact. This study was conducted to reconcile the importance of daycare for child development with the empirical estimates of small effects. Using a random sample of 500 children from 100 daycare centers in the Municipality of Rio de Janeiro (Brazil), the study combines a flexible function relating child development to daycare center quality. A hedonic cost function permits an evaluation of the cost-effectiveness of better-quality daycare centers. The study finds that the developmental age of children attending high-quality services is greater than that of children attending low-quality centers. It also finds that quality improvement can be measured in a number of ways, with different cost implications or impacts on child development.
Keywords: D61; I21; I22; 330